Targeting associated mechanisms of anterior cruciate ligament injury in female community-level athletes - Staynor, J. M.; Nicholas, J. C.; Weir, G.; Alderson, J. A.; Donnelly, C. J. (Sports Biomechanics, 2017)
This study aims to determine if biomechanically informed injury prevention training can reduce associated factors of anterior cruciate ligament injury risk among a general female athletic population. Female community-level team sport athletes, split into intervention (n = 8) and comparison groups (n = 10), completed a sidestepping movement assessment prior to and following a 9-week training period, in which kinetic, kinematic and neuromuscular data were collected. The intervention group completed a biomechanically informed training protocol, consisting of plyometric, resistance and balance exercises, adjunct to normal training, for 15-20 min twice a week. Following the 9-week intervention, total activation of the muscles crossing the knee (n = 7) decreased for both the training (Delta -15.02%, d = 0.45) and comparison (Delta -9.68%, d = 0.47) groups. This decrease was accompanied by elevated peak knee valgus (Delta +27.78%, d = -0.36) and internal rotation moments (Delta +37.50%, d = -0.56) in the comparison group, suggesting that female community athletes are at an increased risk of injury after a season of play. Peak knee valgus and internal rotation knee moments among athletes who participated in training intervention did not change over the intervention period. Results suggest participation in a biomechanically informed training intervention may mitigate the apparent deleterious effects of community-level sport participation.